RNA expression changes driven by altered epigenetics status related to NASH etiology - Castellano Castillo, Daniel; Ramos-Molina, Bruno; Frutos, María Dolores; Arranz-Salas, Isabel María; Reyes-Engel, Armando; Queipo-Ortuño, María Isabel; Cardona-Díaz, Fernando (ELSEVIER, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a growing health problem due to the increased obesity rates, among other factors. In its more severe stage (NASH), inflammation, hepatocellular ballooning and fibrosis are present in the liver, which can further evolve to total liver dysfunction or even hepatocarcinoma. As a metabolic disease, is associated to environmental factors such as diet and lifestyle conditions, which in turn can influence the epigenetic landscape of the cells, affecting to the gene expression profile and chromatin organization. In this study we performed ATAC-sequencing and RNA-sequencing to interrogate the chromatin status of liver biopsies in subjects with and without NASH and its effects on RNA transcription and NASH etiology. NASH subjects showed transcriptional downregulation for lipid and glucose metabolic pathways (e.g., ABC transporters, AMPK, FoxO or insulin pathways). A total of 229 genes were differentially enriched (ATAC and mRNA) in NASH, which were mainly related to lipid transport activity, nuclear receptor-binding, dicarboxylic acid transporter, and PPARA lipid regulation. Interpolation of ATAC data with known liver enhancer regions showed differential openness at 8 enhancers, some linked to genes involved in lipid metabolism, (i.e., FASN) and glucose homeostasis (i.e., GCGR). In conclusion, the chromatin landscape is altered in NASH patients compared to patients without this liver condition. This alteration might cause mRNA changes explaining, at least partially, the etiology and pathophysiology of the disease.
Keywords: Obesidad; Hígado - Etiología; Epigenetics; NASH; Obesity; ATACseq; Chromatin openness; Liver